Draft Genome Sequence of the Vanadium-Leaching Bacterium Pseudomonas chlororaphis Strain L19 (Genome Announc, 2018)
Pseudomonas chlororaphis strain L19, isolated from stone coal soil, has the ability to perform bioleaching to release vanadium ions from mineral ore. Here, we report the draft genome sequence and annotation of the vanadium-leaching bacterium Pseudomonas chlororaphis L19. These data provide information for understanding the genomic properties and mineral bioleaching mechanisms of strain L19.